Implementation of Article 45 of Law No. 1 of 1974 concerning Marriage Related to the Fulfillment of Children's Rights After Divorce Based on the Principle of Legal Certainty - Ginanjar, Yudha (Jurnal Multidisiplin Indonesia, 2024)
This study explores how Article 45 of Law No. 1 of 1974 concerning Marriage is applied to fulfill children's rights after divorce. The main focus of this study is to understand how the principle of legal certainty, which is the legal basis in Indonesia, is implemented in divorce cases, especially related to the fulfillment of children's rights. This study uses a normative juridical method with a legislative approach and secondary data analysis. The results of this study show that although Article 45 of the 1974 UUP explicitly regulated the obligations of parents to fulfill the rights of children after divorce, in practice, there are still various obstacles. These obstacles include a lack of legal understanding and awareness from the parties, as well as gaps in the application of the law that cause children's rights to not be fully fulfilled. This study recommends improving regulations and increasing supervision in implementing existing policies. Thus, it is hoped that children's rights in divorce cases can be better protected, in line with the principle of legal certainty guaranteed by law.